Mathematical modelling of the mechanical response of earth embankments on piled foundations. Issue 9 (4th September 2020) - di Prisco, Claudio; Flessati, Luca; Frigerio, Gabriele; Galli, Andrea
Abstract : Piled foundations are largely employed as settlement reducers in the design of artificial embankments on soft soil strata. The commonly employed design methods are, however, based on simplified approaches not allowing the assessment of average and differential settlements at the top of the embankment. With this objective, the authors introduce a generalised constitutive relationship capable of accounting for irreversibilities stemming from both geometrical evolution and soil yielding. The model derives from the interpretation of the results of a campaign of three-dimensional elastic–plastic finite-difference numerical analyses describing the embankment construction process. Numerous simplifying assumptions (for instance smooth pile shaft, drained conditions) have been employed. Nevertheless, this does not compromise the theoretical value of the proposed approach. From a practical point of view, this model is a useful tool for geotechnical engineers to employ with a displacement-based design perspective.